pegegog 2022
DOI: 10.47750/pegegog.12.03.16
|View full text |Cite
|
Sign up to set email alerts
|

Is symbolic modeling videos containing Malay values effective to improve student’s social harmony?

Abstract: Social harmony stimulations should be given as early as possible since it correlates with a number of conducts, such as respecting cultural differences, tolerance, and willingness to constructively resolve a conflict. As social harmony affects students' characters, an intervention to enhance their social harmony is required. This study aims to investigate the efficiency of symbolic video modeling consisting of Malay values in improving students' social harmony. It used a quasi-experimental design with one grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
4
0
7
Order By: Relevance
“…Sebagaimana diungkapkan oleh (Kadafi et al, 2021) bahwa perempuan lebih teliti dalam bertindak, sehingga mereka memperhatikan setiap langkah yang akan dilakukan. Hasil dari penelitian (Halida, Mappiare-at, et al, 2022) juga mengungkap bahwa harmoni sosial meningkat secara signifikan dan lebih tinggi saat diberikan layanan bimbingan kelompok menggunakan modeling simbolis bermuatan syair gulung.…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations
“…Sebagaimana diungkapkan oleh (Kadafi et al, 2021) bahwa perempuan lebih teliti dalam bertindak, sehingga mereka memperhatikan setiap langkah yang akan dilakukan. Hasil dari penelitian (Halida, Mappiare-at, et al, 2022) juga mengungkap bahwa harmoni sosial meningkat secara signifikan dan lebih tinggi saat diberikan layanan bimbingan kelompok menggunakan modeling simbolis bermuatan syair gulung.…”
Section: Hasil Dan Pembahasanunclassified
“…Salah satu perilaku yang dikembangkan melalui pendidikan karakter di sekolah yaitu dengan cara meningkatkan harmoni sosial melalui berbagai teknik yang mendidik (Halida, Mappiare-at, et al, 2022;Halida, Putri, et al, 2022). Harapan bangsa yaitu menghasilkan generasi muda yang unggul dan berkarakter, maka dalam institusi pendidikan sekolah dituntut untuk memiliki tanggungjawab (Aunurrahman et al, 2014;Halida et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…There are many studies look like (Chan & Wong, 2015;Borowiec et al, 2021;Salavera et al, 2021) that discuss perpetrator, but there are still few that discuss the relationship between victims and bullied victims who have aggressive behavior. There are even studies that have identified three main groups involved in bullying, such as at risk, especially in terms of non-peer victimization, social support, and mental support (Kennedy, 2021;Sourander, 2016;Halida et al, 2022).…”
Section: Rationalementioning
confidence: 99%
“…Sebelum melakukan pengembangan produk, dilakukan pengkajian hasil penelitian terdahulu terkait metode atau teknik untuk meningkatkan perilaku baik dalam fungsi BK pada aspek pencegahan. Adapun hasil penelitian terdahulu mengatakan video modeling bermuatan syair gulung efektif meningkatkan harmoni sosial di kelas VII SMP Kota Pontianak (Halida et al, 2022). Permainan ular tangga meningkatkan tanggungjawab siswa SMP (S. Putri & Ramli, 2016).…”
Section: Gambar3 Link Video Kesenian Tundang Gambar 4 Video Menuturka...unclassified